2012
DOI: 10.1080/14697688.2011.573496
|View full text |Cite
|
Sign up to set email alerts
|

Pricing the Chicago Board of Trade T-Bond futures

Abstract: The aim of this paper is to investigate the pricing of the Chicago Board of Trade (CBOT) Treasury-Bond futures. The difficulty in pricing it arises from its multiple inter-dependent embedded delivery options, which can be exercised at various times and dates during the delivery month. We consider a general Markov diffusion process model for stochastic interest rates and propose a pricing algorithm that can handle all the delivery rules embedded in the CBOT T-Bond futures. Our procedure combines dynamic program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…R Ben-Abdallah, H Ben-Ameur and M Bretor (2012) took into account the option to choose time and the option to choose bonds for the treasury bond futures contract pricing and used Vasicek model, CIR model and HW models for modeling the spot interest rate to give Numerical solution of treasury bond futures prices. The study found that in the two months before the delivery time, the market price of treasury bond futures is lower on average about 2% than the theoretical price, indicating that if the HW model is suitable for the modeling of interest rates, the market overestimated the value of the option selected bonds [14].…”
Section: Futures Pricing Theoriesmentioning
confidence: 99%
“…R Ben-Abdallah, H Ben-Ameur and M Bretor (2012) took into account the option to choose time and the option to choose bonds for the treasury bond futures contract pricing and used Vasicek model, CIR model and HW models for modeling the spot interest rate to give Numerical solution of treasury bond futures prices. The study found that in the two months before the delivery time, the market price of treasury bond futures is lower on average about 2% than the theoretical price, indicating that if the HW model is suitable for the modeling of interest rates, the market overestimated the value of the option selected bonds [14].…”
Section: Futures Pricing Theoriesmentioning
confidence: 99%
“…There is not much literature on the exercise of the strategic timing options embedded in the U.S. T‐Bond futures, and most of it is concerned with their pricing in conjunction with the quality option (see, for instance, Ben‐Abdallah, Ben‐Ameur, & Breton, ; Biagini & Björk, ; Boyle, ; Chen & Yeh, ; Chen, Ju, & Yeh, ; Cohen, ; Hedge, ; Hemler, ; Kane & Marcus, ). However, because of the complexity arising from taking all the embedded delivery options into account simultaneously, not much has been said about the optimal timing strategy, apart from rules of thumb that have been suggested for early delivery (see Burghardt, Belton, Lane, & Papa, ; Choudhry, ).…”
Section: Introductionmentioning
confidence: 99%